Estudo imuno-histoquímico da expressão da GLUT-1 e mensuração do índice angiogênico (CD34) em adenomas pleomórficos, carcinomas adenóides císticos e carcinomas mucoepidermóides de glândulas salivares - Oliveira, Lucileide Castro de (2012)
The expression of glucose transporter protein 1 (GLUT-1), as well the angiogenesis has been associated to clinical behavior and aggressiveness in tumors of various origin. It is believed that the expression of this protein denotes metabolic demand of the tumor cells and, thus its influence upon the formation of new blood vessels. Pleomorphic adenoma (PA) and the adenoid cystic carcinoma (ACC) and mucoepidermoid carcinoma (MEC) represent, respectively, the most commom benign and malignant tumors of salivary glands. The aim of this study was to analyze and compare the immunohistochemical expression of GLUT-1 and its correlation with angiogenesis in cases of PAs, ACCs and MECs considering their histological grades. The sample consisted of 20 PAs, 20 ACCs and 10 MECs. The cases were analyzed and classified according to their histological grades. The expression of GLUT-1 was evaluated in the parenchyma lesions, establishing the percentage of immunopositive cells, according to the following scores: 0 (no cell immunomarked), 1 (up to 25% of tumor cells immunostained), 2 (25 - 50% of tumor cells immunostained) and 3 (more than 50% of tumor cells immunostained). The angiogenic index was analyzed by counting the microvessels immunostained by anti-CD34 antibody, in 5 fields (200X). The analysis of the expression of GLUT-1 in tumor parenchyma showed statistically significant differences between benign and malignant groups (p = 0.022). The average number of microvessels in PAs was 40.4, 21.2 in ACCs and 66.5 in MECs, with significant differences between groups (p <0.001). When compared to the expression of GLUT-1 and angiogenic index as a whole, there was no significant correlation between the number of microvessels and the expression of GLUT-1 (r = 0.211, p = 0.141). In conclusion, the results of this study suggest not only that differences in biological behavior between PAs, ACCs and MECs may be associated to the expression of GLUT-1, but also that benign and malignant salivary gland present differences in the average number of microvessels, with higher levels considered more aggressive tumors. Furthermore, the number of newly formed microvessels can be independent of the metabolic demand of the tumor cells